(3OjhGf GHf SfGf GdNaGLjs - (3YHO Gddg Hf eMeO Hf SYjO Hf SfGf, CHh eMeO GdNaGLj GdMdHj,J (B466 (3g` s ((3efUhQ GdYWGQ s)
(3ChdgG (B:s
(3bGd jQKj CHG GdMSf Ydj Hf eMeO Hf YjSi GdcGJH, hbO obJd hUdH(B: (3heYPd LGQ Ydi ZdhGFg jQhj MOjK fOGg Yf CYOGFg s
(3BNQgG (B:s
(3jG eabOG eGA GdLahf hcfJ Cfabg Ydjg Ef de Jcf Yjfj aCfJ CYR ef fXQJ Edjg s
(3fSNI KGfjIs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B122 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B120s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B3 - (3U (B123 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B788s
Keywords: (3GdCOHs